1990
DOI: 10.1159/000125535
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Affects the Luteinizing Hormone Secretory Pattern in the Short- and Long-Term Ovariectomized Rat

Abstract: The effect of naloxone, an opiate receptor antagonist, on the secretory pattern of luteinizing hormone (LH) was evaluated in 4-, 16- and 32-week ovariectomized (OVX) rats. Freely moving rats bearing cardiac cannulae were bled every 6 min for 3 h. During the first 90 min of bleeding, an equal volume of saline was injected after withdrawal of each blood sample, while during the second 90 min the replacement was done with saline containing naloxone at a dose of 0.5 (lower dose) or 1.0 (higher dose) mg/kg/h; stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…The interpulse interval of GnRH pulses which occur in GnRH neurons derived from the olfactory placode of rat embryos, approximately 30 min, was very similar to that observed in LH in ovariectomized adult female rats in vivo [19, 25, 26]. The same characteristics of GnRH neurons cultured after being derived from the olfactory placode of embryos were observed in rhesus monkeys [10].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The interpulse interval of GnRH pulses which occur in GnRH neurons derived from the olfactory placode of rat embryos, approximately 30 min, was very similar to that observed in LH in ovariectomized adult female rats in vivo [19, 25, 26]. The same characteristics of GnRH neurons cultured after being derived from the olfactory placode of embryos were observed in rhesus monkeys [10].…”
Section: Discussionmentioning
confidence: 56%
“…A GnRH pulse was defined by the method used for detection of the LH pulse [18, 19]. CVs were determined for all the GnRH values that constituted the ascending and descending phases of each potential GnRH pulse.…”
Section: Methodsmentioning
confidence: 99%
“…Funabashi et al (16) reported that, in ovx rats, intermittent administration of naloxone in the same dose as we used resulted in a significant increase in the mean LH concentration. Kimura et al (17) reported that the same intermittent administration of naloxone in ovx rats significantly increased the frequency and the duration of multiunit activity volleys that accompanied the initiation of each LH pulse.…”
Section: Figurementioning
confidence: 73%
“…Blood samples (0.3 ml) were taken every 6 min for 2 h through the intra-atrial cannula and an equal volume of heparinized saline containing naloxone (Sigma Chemical Co., St Louis, MO, USA) (0.5 mg/kg per h) or heparinized saline only was replaced after each bleeding (16,17). Rats were divided into three experimental groups: group 1, 3V saline þ i.v.…”
Section: Administration Of 2-b4omentioning
confidence: 99%
“…Microinjections were performed immediately after the end of the first 90-min control sampling in OVX rats and at 1300 h after control sampling in proestrous rats. The other procedures are the same as reported previously [7] including the analysis of LH pulsatility [11,12].…”
Section: Methodsmentioning
confidence: 99%